2021
DOI: 10.1016/j.ynstr.2021.100342
|View full text |Cite
|
Sign up to set email alerts
|

Stress induces microglia-associated synaptic circuit alterations in the dorsomedial prefrontal cortex

Abstract: The mammalian dorsomedial prefrontal cortex (dmPFC) receives diverse inputs and plays important roles in adaptive behavior and cognitive flexibility. Stress, a major risk factor for many psychiatric disorders, compromises the structure and function of multiple brain regions and circuits. Here we show that 7-day restraint stress impairs reversal learning in the 4-choice odor discrimination test, a decision-making task requiring an intact dmPFC. In vivo two-photon imaging further reveals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 104 publications
(136 reference statements)
2
9
0
Order By: Relevance
“…Consistent with prior studies, we found that CUS increased microglia-mediated remodeling of apical dendrites in the mPFC [2, 3]. Genetic loss or pharmacological blockade of microglial P2Y12 prevented microglia-mediated neuronal remodeling and attenuated synapse loss in the mPFC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with prior studies, we found that CUS increased microglia-mediated remodeling of apical dendrites in the mPFC [2, 3]. Genetic loss or pharmacological blockade of microglial P2Y12 prevented microglia-mediated neuronal remodeling and attenuated synapse loss in the mPFC.…”
Section: Discussionsupporting
confidence: 91%
“…Clinical and preclinical findings suggest that microglia, the brain-resident macrophages, may contribute to synaptic alterations in the PFC and MDD-associated symptoms. In fact, chronic stress has been shown to induce microglia-mediated remodeling of synapses in the medial PFC (mPFC) of mice and subsequent deficits in PFC-mediated behaviors, including working memory function and cognitive flexibility [2, 3]. Despite these findings, relatively little is known regarding the pathways that drive microglia-neuron interactions in stress and microglial interventions in stress-linked disorders remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the enhanced and prolonged recruitment of activated microglia processes to the site of photodamage was directly involved in synaptic elimination. This is in line with accumulated evidence obtained in animal models of ischemia (Wake et al, 2009), systemic in ammation (Chen et al, 2014;Gallo et al, 2022), stress (Liu et al, 2021) and AD (Gervais et al, 2021;Gratuze et al, 2021;Wright et al, 2013). Together, these ndings complement previous studies and support the hypothesis that early in ammatory changes may lead to synaptic loss and therefore contribute to the cognitive impairment in neurodegenerative diseases such as AD.…”
Section: Discussionsupporting
confidence: 90%
“…Microglia, known as “brain gardeners,” have been found to influence neuronal proliferation, differentiation, and maturation [ 65 , 66 , 67 ]. Microglial morphology is closely linked to microglial functions [ 68 , 69 ], and changes in microglial phenotype are related to the impairment of hippocampal neurogenesis under pathological conditions [ 70 ]. In the healthy brain, microglia have a ramified morphology with a small soma and fine processes [ 68 ].…”
Section: Discussionmentioning
confidence: 99%